Equilibrium modeling in adsorption of Re and Mo ions from single and binary aqueous solutions on Dowex 21K resin - Fathi, M.; Rezai, B.; Keshavarz Alamdari, E.; Alorro, Richard (Taylor & Francis, 2018)
The present study deals with the competitive adsorption of rhenium (Re) and molybdenum (Mo) ions onto Dowex 21K from single component and binary systems. The equilibrium adsorption data were obtained at different initial concentrations (50–250 mg/l), 12 h contact time, 290 K temperature, and resin dosage of 0.05 g at pH around 0.5. The single system equilibrium adsorption data were fitted via non-linear regression techniques to Langmuir, Freundlich, Temkin, and Dubinin–Radushkevich (D–R) isotherm models. Both Freundlich and D–R isotherms for Re and Langmuir and D–R isotherms for Mo suitably described the adsorption equilibrium data. Equilibrium isotherms for the binary adsorption of Re and Mo ions onto Dowex 21K have been analyzed using Extended Langmuir, Modified Langmuir, Extended Freundlich and Langmuir–Freundlich models. The competitive Extended Freundlich model fitted the binary adsorption equilibrium data satisfactorily and adequately. Results of investigation on the mutual interference effects of Mo ions on Re adsorption capacity indicated that although Dowex 21K has generally higher affinity toward Re ions, the adsorption of perrhenate ions () is suppressed by a factor of about 49% in the presence of molybdenum ions. The adsorption of perrhenate ion is affected by competitive inhibition and shield preventing effects.